2011
DOI: 10.1590/s0104-07072011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Atividades de formação do enfermeiro no âmbito da atenção básica à saúde

Abstract: RESUMO:Este estudo teve como objetivo caracterizar oportunidades vivenciadas e atividades realizadas durante as aulas práticas e estágios na atenção básica durante a formação do enfermeiro. A pesquisa do tipo exploratória não probabilística teve coleta de dados no período de fevereiro a março de 2009, por aplicação de questionário semiestruturado a um grupo amostral de 231 acadêmicos matriculados no último ano do curso de graduação em enfermagem de seis Instituições de Ensino Superior de Curitiba-PR. Foram ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
11
Order By: Relevance
“…All seem concerned with detecting relative weakness in the corpus of knowledge built during the course and also with relative uncertainty regarding the actual link between this knowledge and practical experiences (17) .…”
Section: Discussionmentioning
confidence: 99%
“…All seem concerned with detecting relative weakness in the corpus of knowledge built during the course and also with relative uncertainty regarding the actual link between this knowledge and practical experiences (17) .…”
Section: Discussionmentioning
confidence: 99%
“…10 The territorialization actions are the basis to reach the community orientation principle and to understand the territory concept, risk area and microarea. 21 And another study, on the assessment by the users of the presence of students in the family healthcare unit, made a similar finding. The clients indicated that most of the students recognize the importance of valuing the community's knowledge.…”
Section: ] You Get To Know Your Community and It's Important To Knomentioning
confidence: 66%
“…We expect that these activities are approached beyond the technical focus in training and associated to the programming of healthcare actions, such as the National Immunization Program. 21 As regards the home visits, the students enlarge their knowledge about home care and understand the bases on which it is made. It is clear, therefore, that home care must be part of the Nursing Graduation, area that represents a wide action field in growing process, but that requires skilled professionals to perform it.…”
Section: ] You Get To Know Your Community and It's Important To Knomentioning
confidence: 99%
“…Isso pode estar relacionado ao fato de que os graduandos, nos períodos finais do curso, sentem a necessidade de complementar sua formação para atuar no mercado de trabalho e procuram participar de treinamentos e capacitações para adquirir mais experiência e melhor preparo (21) . A quantidade de períodos cursados implica no avanço de componentes curriculares cumpridos e, consequentemente, maior contato do acadêmico com conteúdos e práticas, além do maior tempo para participação em atividades complementares e extracurriculares, ampliando o conhecimento dos discentes, o que foi mostrado neste estudo.…”
Section: Discussionunclassified